Ketamine Use for Successful Resolution of Post-ERCP Acute Pancreatitis Abdominal Pain - Suneel M. Agerwala; Divya Sundarapandiyan; Garret Weber (Case Reports in Anesthesiology)
We report a case in which a patient with intractable pain secondary to post-endoscopic retrograde cholangiopancreatography (ERCP) acute pancreatitis is successfully treated with a subanesthetic ketamine infusion. Shortly after ERCP, the patient reported severe stabbing epigastric pain. She exhibited voluntary guarding and tenderness without distension. Amylase and lipase levels were elevated. Pain persisted for hours despite hydromorphone PCA, hydromorphone boluses, fentanyl boluses, and postprocedure anxiolytics. Pain management was consulted and a ketamine infusion was trialed, leading to a dramatic reduction in pain. This case suggests that ketamine may be a promising option in treating intractable pain associated with ERCP acute pancreatitis.